PENGGUNAAN MEDIA VIDEO ANIMASI PADA MATERI HEWAN DAN TUMBUHAN DI LINGKUNGAN RUMAHKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 16 PIDIE - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to improve the learning outcomes of fourth grade students of MIN 16 Pidie on animal and plant material in my home environment by using animated video media. The type of research is Classroom Action Research. The subjects of the study were grade IV students, totaling 12 students consisting of 7 male students and 5 female students with heterogeneous abilities. This research was conducted in 3 cycles using observation, test, and documentation techniques. The average score of students in the first cycle is 65.8 with 3 students' accuracy or 25% of all students. In the second cycle, the average score of students became 74.16 with student completeness as many as 8 students or 66.7% of the total students. In the third cycle, the average score of students became 90.83 with student completeness as many as 12 students or 100%.